Influence of surface roughness and force on real contact area Busan - Shukla, Abhay Rammurti; Song, Jian
• Surface roughness has significant influence on contact area • Real contact area can be predicted with good precision by simplifying roughness model using core roughness Rk and average groove width RSM • Higher precision can be achieved by proper selection of material ratio • The proposed method can be effectively used for predicting contact resistance for given contact conditions